Pyrimidine dimer excision in Escherichia coli strains deficient in exonucleases V and VII and in the 5' leads to 3' exonuclease of DNA polymerase I. - Chase, J W (1979)
An isogenic series of Escherichia coli strains deficient in various combinations of three 5' leads to 3' exonucleases (exonuclease V, exonuclease VII, and the 5' leads to 3' exonuclease of DNA polymerase I) was constructed and examined for the ability to excise pyrimidine dimers after UV irradiation. Although the recB and recC mutations (deficient in exonuclease V) proved to be incompatible with the polA(Ex) mutation (deficient in the 5' leads to 3' exonuclease of DNA polymerase I), it was possible to reduce the level of the recB,C exonuclease by the use of temperature-sensitive recB270 recC271 mutants. It was found that, by employing strains deficient in exonuclease V, postirradiation DNA degradation could be reduced and dimer excision measurements could be facilitated. Mutants deficient in exonuclease V were found to excise dimers at a rate comparable to that of the wild type. Mutants deficient in exonuclease V and the 5' leads to 3' exonuclease of DNA polymerase I are slightly slower than the wild type at removing dimers accumulated after doses in excess of 40 J/m2. However, although strains with reduced levels of exonuclease VII excised dimers at the same rate as the wild type, the addition of an exonuclease VII deficiency to a strain with reduced levels of exonuclease V and the 5' leads to 3' exonuclease of DNA polymerase I caused a marked decrease in the rate and extent of dimer excision. These observations support previous indications that the 5' leads to 3' exonuclease of DNA polymerase I is important in dimer removal and also suggest a role for exonuclease VII in the excision repair process.